EVALUASI PROGRAM CORPORATE SOSIAL RESPONSIBILITY PADA PT. DJARMA ARU DI WANAAM - Alexander Phuk Tjilen; Maria Veronica Irine Herdjiono (Universitas Musamus,Merauke,Papua, 2012)
Background research on the motivation of companies implementing Corporate Social Responsibility (CSR) is a researcher look at the companies in Indonesia, many CSR activities, even advertise their activities, but whether the long-term benefits that are directly impacting stakeholders. This study used a qualitative approach that is the case study, to investigate a specific phenomenon that takes into account the elements of time, place and circumstances in which this phenomenon occurs in order to obtain a thorough and in-depth understanding of the phenomenon. The results showed that the application of CSR by PT. Djarma Aru was successful, because the local community has much to gain, though still undeniably a counter opinion on the success of the CRS. Implementation of CSR by companies have reached the stage of Corporate Citizenship, but in this application the company experienced a number of problems both internal and external PT. Djarma Aru has experienced ups and downs of business related to CSR, but the results obtained are quite satisfactory because with the passage of CSR companies can run well and got pretty good support from the community, although there is no denying the community and local government still expects more of which has been executed.